Defect engineering and alloying strategies for tailoring thermoelectric behavior in GeTe and its alloys - Qiyong Chen; Cheng Yang; Tong Xing; Jinyang Xi; Wenqing Zhang; Jiong Yang; Lili Xi (Journal of Materiomics)
GeTe exhibits excellent p-type medium-temperature thermoelectric properties with low toxicity and good mechanical characteristics, making it highly promising for development in the thermoelectric field. However, GeTe is prone to producing Ge vacancies, leading to high p-type carrier concentration, which results in elevated electronic thermal conductivity and a low Seebeck coefficient. This study systematically analyzes intrinsic and extrinsic defects in GeTe and its alloys, focusing on reducing p-type carrier concentration through first-principles calculations. The results reveal that substituting Ge-sites with Bi (BiGe) yields lower donor defect formation energy, effectively reducing p-type carrier concentration of GeTe and its alloys compared to other elemental doping. Additionally, alloying with certain elements, such as Pb, proves favorable for decreased p-type carrier concentration due to lowered energy levels of valence band maximum (VBM). Inspired by this, screening divalent elements for alloying on Ge-sites reveals that Sr, Ba, Eu, and Yb substantially reduce the VBM of GeTe. Further calculations for Ba and Yb-alloyed GeTe confirm changes in formation energies for donor (favorable) and acceptor (unfavorable) defects. Our work provides a systematic investigation of intrinsic and various extrinsic doping defects in GeTe and its alloys, shedding light on possible strategies of optimizing carrier concentration in these compounds.